Graphene-based saturable absorber and modelocked laser behaviors under gamma-ray radiation - Kim, Dohyun; Park, Nam Hun; Lee, Hyunju; Lee, Jaegoan; Yeom, Dong Il; Kim, Jungwon (Photonics Research, 2019)
We investigate optical and electrical behaviors of a graphene saturable absorber (SA) and mode-locking performance of a graphene-SA-based mode-locked Er fiber laser in gamma-ray radiation. When irradiated up to 4.8 kGy at ~100 Gy/hr dose rate, the overall nonlinear transmittance in transverse electric mode was increased, while maintaining modulation depth to >10%. The corresponding polarization-dependent loss was reduced at a 1.2-dB/kGy rate. In the electrical properties, the charge carrier mobility was reduced, and the Dirac voltage shift was increased to positive under gamma-ray radiation. The radiation-induced optical and electrical changes turned out to be almost recovered after a few days. In addition, we confirmed that the graphene-SA-based laser showed stable CW mode-locking operation while the inserted graphene SA was irradiated for 2-kGy at a 45-Gy/hr dose rate, which corresponds to >40 years of operation in low Earth orbit satellites. To the best of our knowledge, this is the first evaluation of graphene SAs and graphene-SA-based mode-locked lasers in gamma-ray radiation, and the measured results confirm the high potential of graphene SAs and graphene-SA-based lasers in various outer-space environments as well as other radiation environments, including particle accelerators and radiationbased medical instruments.
Keywords: Electrical behaviors; Graphene saturable absorbers; Low earth orbit satellites; Medical instruments; Nonlinear transmittance; Polarization dependent loss; Radiation environments; Transverse electric modes